Using discrete event simulation to investigate engineering product service strategies - Ball, Peter D.; Alabdulkarim, Abdullah; Cuthbert, Rachel; Thorne, Alan (Cranfield University, 2010)
As companies develop business models based on service provision through engineering products the role of information becomes increasingly important to achieving high levels of service performance. One approach to achieving higher levels of service performance is to deploy sensing technology in the product to provide the service operation with diagnostic and prognostic information. Simulation modelling techniques are able to capture operational performance of complex systems involving product and information flows and are therefore appropriate to modelling such service provision. This paper documents work carried out in this area and demonstrates the application of simulation when providing a service through engineered products. It would seem logical that receiving increasing product performance information would enable higher levels of service performance to be achieved. The work here shows how performance can be captured and the circumstances in which diagnostic and prognostic information is beneficial as well as when it has little effect.